Tamoxifen Initiation After Ductal Carcinoma In Situ. (14th January 2016) - Nichols, Hazel B.; Bowles, Erin J.A.; Islam, Jessica; Madziwa, Lawrence; Stürmer, Til; Tran, Diem‐Thy; Buist, Diana S.M.
Abstract : Background: Endocrine therapy initiation after ductal carcinoma in situ (DCIS) is highly variable and largely unexplained. National guidelines recommend considering tamoxifen for women with estrogen receptor‐positive (ER+) DCIS or who undergo excision alone. We evaluated endocrine therapy use after DCIS over a 15‐year period in an integrated health care setting to identify factors related to initiation. Methods: Female Group Health Cooperative enrollees ages 18–89 years with a DCIS diagnosis during 1996–2011 were eligible for inclusion. Endocrine therapy was identified through pharmacy records. Tumor and treatment information were from tumor registry reports; demographics and other risk factors were from questionnaires and electronic medical records. Relative risks (RRs) and 95% confidence intervals (CIs) for endocrine therapy initiation were calculated using multivariable generalized linear models. Results: We identified 727 women with a DCIS diagnosis, including 163 (22%) who initiated endocrine therapy (149 tamoxifen, 14 aromatase inhibitor). Younger women were more likely to initiate endocrine therapy (RR 1.69; 95% CI 1.16–2.46 for ages 45–54 vs. 65–74 years). Compared with breast‐conserving surgery (BCS) with radiation, women who had BCS alone (RR 0.46; 95% CI 0.25–0.84) or mastectomy (RR 0.54; 95% CI 0.39–0.75) were less likely to use endocrine therapy. ER testing increased from 4% of DCIS cases in 2001 to 71% in 2011; however, endocrine therapy initiation decreased from 58% of ER+ DCIS in 2001–2005 to 37% in 2009–2011. Conclusion: Increasing ER testing since 2001 has not corresponded to parallel increases in endocrine therapy initiation. Age, surgery, and radiation were the primary factors associated with initiation. Implications for Practice: National guidelines recommend considering tamoxifen for women with ductal carcinoma in situ (DCIS) who are estrogen receptor‐positive (ER+) or who undergo excision alone. In this study, the rapid increase in ER testing caused by tamoxifen's approval in 2000 did not lead to increases in endocrine therapy initiation, despite recognition of an increasing number of DCIS tumors as ER+ each year. Contrary to the suggested guidelines, women who had breast‐conserving surgery without radiation were less likely to use tamoxifen than those who had radiation. Future Food and Drug Administration approval of new endocrine agents for DCIS (such as aromatase inhibitors) may provide an opportunity to reemphasize benefits by ER and surgery status. Abstract : In this study, which evaluated endocrine therapy use after ductal carcinoma in situ (DCIS) over a 15‐year period, 163 of 727 women with a DCIS diagnosis (22%) initiated endocrine therapy. Age, surgery, and radiation were the primary factors in initiation, but increased estrogen receptor testing has not resulted in corresponding increases in endocrine therapy.